Islamic Economic Model as a Solution for Achieving Sustainable Development: Social and Environmental Impacts - Marlina, Teti (Fast in Social Sciences, 2025)
Sustainable development has become a global agenda that demands integration between a growing economy, social justice, and environmental preservation. In facing challenges, Islamic economics offers a holistic solution with sharia principles that emphasize social justice, environmental responsibility, and wise management of natural resources. This article aims to analyze the contribution of Islamic economics to achieving sustainable development objectives, focusing on the social and environmental impacts generated. Research. This approach uses qualitative and analytical literature to study the role of instruments in Islamic economics, such as zakat, waqf, and green sukuk, in support of achieving the objective of sustainable development. Research results show that zakat plays an important role in alleviating poverty and reducing social inequality, waqf supports projects that are socially friendly and have a positive impact on the environment, while green sukuk contributes to funding energy-focused, renewable, and conservation projects. Applying Sharia principles in Islamic economics also encourages management to adopt a power-efficient nature, reducing pollution, and ensuring environmental sustainability. This article concludes that integrating Islamic economics in policy development can speed up the achievement of SDGs (Sustainable Development Goals), giving more solutions for a fair, inclusive, and friendly environment. For that, there is a need to strengthen the implementation of supportive policies in Islamic economics and utilize more of the instruments of Islamic economics to push for a sustainable, fair, and friendly economic environment.